(2x+1)(x-2) = 2x^2 - 4x +x -2= 2x^2-3x-2
Answer:
x>-2
Step-by-step explanation:
first you want to get rid of all of the numbers on the left so you can only be left with 2x>-4 then you decide both sides by 2x because you only want to be left with one x and once you divide you will be left with x>-2
Answer:
2.14 or 214/100
Step-by-step explanation:
Answer:
12
Step-by-step explanation:
So, the 24cm, is the diameter, a little circle autonomy here, the diameter is the length across the circle, and the radius is to the mid point, or half-way point, which means that the radius is half the diameter, so, 24 ÷ 2 = 12
hope this helps:)
Answer:
a
Step-by-step explanation:
(2x + 3y)²
= (2x + 3y)(2x + 3y)
Each term in the second factor is multiplied by each term in the first factor
2x(2x + 3y) + 3y(2x + 3y) ← distribute parenthesis
= 4x² + 6xy + 6xy + 9y² ← collect like terms
= 4x² + 12xy + 9y² → a